Nucleotide trapping at the ATPase site of myosin subfragment 1 by a new interthiol crosslinking. - Chaussepied, P (1986)
When myosin subfragment 1 derivatives in which the reactive sulfhydryl SH1 has been blocked react with N,N'-p-phenylenedimaleimide or 5,5'-dithiobis(2-nitrobenzoic acid), the reactive sulfhydryl group SH2 of the 20-kDa domain is crosslinked with a thiol of the 50-kDa domain of the heavy chain. The crosslink induces the stable trapping of a significant amount of Mg2+-nucleotide in the ATPase site.